Development of a Remote Mediterranean Diet Intervention for Patients With Cancer During Chemotherapy Treatment: A Mixed Methods Analysis. (14th June 2022) - Kleckner, Amber; Peppone, Luke; Youngblood, Shari; Reschke, Jennifer
Abstract: Objectives: The Mediterranean Diet (MedDiet) is rich in fruit, vegetables, whole grains, and bioactive compounds. Despite emerging research on the benefits of nutrition to complement the efficacy of chemotherapy and reduce symptom burden, there are few structured nutritional programs available for patients with cancer. Herein, we developed a MedDiet intervention for patients undergoing chemotherapy and identified barriers and facilitators to adherence. Methods: This was a qualitative analysis of the intervention arm of a randomized controlled trial (NCT04534738). Participants were eligible if they had cancer (any type) and had at least 6 weeks of chemotherapy scheduled. The 8-week MedDiet intervention included home food delivery (frozen meals and MedDiet ingredients for the first 4 weeks), education, goal-setting, a cookbook, and weekly phone calls with a nutritionist. MedDiet adherence was measured using the MedDiet Adherence questionnaire at baseline, 4 weeks, and 8 weeks; change from baseline was assessed using paired t-tests at 4 and 8 weeks. After completion of the study, participants underwent a semi-structured interview to provide feedback on the program. Interviews were transcribed and themes were identified using emergent coding. Results: Participants (n = 23) were 52.5 ± 13.6 years old, 91% female, and 83% White. Participants had breast (87%) or another type of cancer. MedDiet adherence score increased from 4.0 ± 2.7 at baseline to 6.7 ± 2.8 at 4 weeks and 6.5 ± 2.6 at 8 weeks (both p < 0.001). Interviews were conducted with 21 patients. While most participants (n = 15, 71%) did not actively seek nutritional information before treatment, most (n = 19, 90%) were highly engaged with the MedDiet program. Many (n = 11) volunteered feelings of empowerment and/or a welcomed a sense of control. Facilitators to adherence included accountability, structure, provision of food, palatability, and easy adoption. Barriers included chemotherapy-induced taste changes and mouth sores, others preparing food for the patient, cooking for family members' preferences, and mental burden. Conclusions: A remote MedDiet intervention was effective and well received by patients undergoing chemotherapy. Future research should investigate how a MedDiet intervention affects clinical outcomes and symptom burden. Funding Sources: NIH National Cancer Institute.